IMF Conditionality : Experience Under Stand-By and Extended Arrangements, Part II: Background Papers - Bennett, Adam (Occasional Papers; Occasional Paper, 1995)
This paper is part II of a two-volume study conducted as a part of the IMF's ongoing process of evaluating its lending facilities. It focuses on IMF-supported programs and macroeconomic performance during 1988-92, reflecting information available through the end of 1993. Part I (Occasional Paper No. 128) provides an overview of the principal issues and findings and distills the main message for future programs. Part II presents detailed examinations of selected policy issues in five background papers.